Decolonise oral health care: calling for a rights-based, accountability framework approach - Foláyan, Moréniké Oluwátóyìn; Cachagee, Madison; Poirier, Brianna; Booth, Joelle; Neville, Patricia; Naresh, Arish; Fleming, Eleanor (Frontiers in Oral Health, 2025)
This paper explores how colonisation has shaped oral healthcare and oral health inequities across Indigenous populations globally. It highlights how colonial healthcare models, which prioritise Western medical paradigms, often marginalise Indigenous knowledge and practices. For Indigenous communities, such as Aboriginal Australians, Māori, and those in the Global South, oral health disparities stem from historical and ongoing structural violence, socioeconomic barriers, and limited access to culturally appropriate care. The authors argue for a decolonisation framework in global oral health that shifts power, accountability, and respect toward Indigenous and marginalised communities. A rights-based, accountability-informed decolonisation framework seeks to address historical and ongoing oral health inequities, integrating a view that oral health is a human right and demands that governments and health systems rectify the disparities. It emphasises culturally relevant care and inclusive policymaking, fostering solidarity and systemic change to create equitable and effective oral healthcare for all populations. We propose that deliberate actions need to be taken to centre power redistribution, accountability, and respect in global oral health, moving away from Euro-American-centric frameworks to create an equitable, culturally responsive oral healthcare system. Our calls to action include the need for self-reflection within the field to dismantle entrenched colonial ideologies and prioritise Indigenous leadership and knowledge. Effective allyship should involve collaboration driven by the needs of communities, with institutions accountable for reducing exclusionary practices. By “learning to unlearn” traditional frameworks, the oral health community can build a system that genuinely addresses health disparities and supports justice and equity worldwide.